2014
DOI: 10.1118/1.4890592
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of Acuros XB, AAA, and XVMC in stereotactic body radiotherapy for lung cancer

Abstract: In the phantom evaluations, AXB and XVMC agreed better with measurements than did AAA. Calculations differed in the density-changing zones (substance boundaries) between AXB/XVMC and AAA. In the lung SBRT cases, a comparative analysis of dose-volumetric data and dose distributions with XVMC demonstrated that the AXB provided better agreement with XVMC than AAA. The computation time of AXB was faster than that of XVMC; therefore, AXB has better balance in terms of the dosimetric performance and computation spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 19 publications
10
59
0
Order By: Relevance
“…In all cases, AXB exhibited closer agreement with MC calculations than AAA and the differences were generally less than 5%. The results of these studies support the hypothesis that AXB produces more accurate dose calculations in heterogeneous materials and has led to follow‐up clinical application studies into the implications of using AXB in lung treatment planning 13, 15, 16, 17, 18. The irradiation volume in whole breast radiotherapy is quite inhomogeneous with severe contour changes.…”
Section: Discussionsupporting
confidence: 61%
“…In all cases, AXB exhibited closer agreement with MC calculations than AAA and the differences were generally less than 5%. The results of these studies support the hypothesis that AXB produces more accurate dose calculations in heterogeneous materials and has led to follow‐up clinical application studies into the implications of using AXB in lung treatment planning 13, 15, 16, 17, 18. The irradiation volume in whole breast radiotherapy is quite inhomogeneous with severe contour changes.…”
Section: Discussionsupporting
confidence: 61%
“…The Acuros XB algorithm, a numerical method based on linear Boltzmann transport equation solver, is also available in the Eclipse TPS. The algorithm has been compared to the AAA in numerous studies, and demonstrated that it has better agreement with full MC simulation in slab phantoms containing various materials 49 , 50 . Rana et al (51) reported the dose calculation using the Acuros XB had better agreement with the measurement than using the AAA in the inhomogeneous phantoms.…”
Section: Discussionmentioning
confidence: 99%
“…Fogliata et al reported that up to 2% of dose deviation from AAA with high energy beams. 57 Tsuruta et al 58 found that AXB yielded more accurate dose calculations that were closer to those with Monte Carlo than did AAA in lung SBRT cases. Our previous research also indicated that dose difference between AXB and AAA in lung and tumour regions was different.…”
Section: Discussionmentioning
confidence: 99%